THRIFT SHOPPING SEBAGAI ALTERNATIF KONSUMSI FASHION MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS UDAYANA - Suarningsih, Ni Kadek; Nugroho, Wahyu Budi; Krisna Aditya, I Gusti Ngurah Agung (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
Thrift shopping is an activity that is now increasingly popular as a substitute or alternative in fashion consumption the existence of thrift shops that are increasingly spreading and the number of parties especially celebrities, are increasingly introducing this activity, causing thrift shopping to be increasingly popular, especially among teenagers, namely female students. A qualitative approach, descriptive explanatory type with James S. Coleman’s rational choice theory and Pierre Felix Bourdieu’s habitus theory were used to analyze this activity. Alternative consumption of fashion thrift according to the student of the Faculty of Social and Political Sciences Udayana University as an informant is the most rational action taken. This is in accordance with the objectives that have been set. Using a little capital but the maximum success of the action is a form of rationality of action for the informants. Keywords: Student, Thrift Shopping, Alternative Fashion Consumption